DYNAMIC NATURE OF HYDROLOGICAL SIMILARITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Nowadays, there is a growing interest in understanding how water bodies and their catchments react to environment, landscape and climate change. Runoff change is an integral indicator of climate and landscape changes. Similar landscapes form a similar hydrological catchment response to precipitation. The algorithm for identification of homogeneous groups of catchments (in terms of hydrometeorology) has been developed and tested. The 26 catchments studied are situated in the south-eastern part of the Baltic Sea Basin. Observational data from 1986 to 2016 were used for cluster analysis. Catchments clustering over three consecutive ten-year periods has shown some variability in the clusters content due to changes in the hydrological response of the study catchments. The results obtained were analyzed based on both hydrogrometeorological and landscape characteristics.